The Predominance of Klebsiella aerogenes among Carbapenem-Resistant Enterobacteriaceae Infections in Japan - Kosuke Kamio; J. Luis Espinoza (Pathogens, 2022)
The emergence of carbapenem-resistant Enterobacteriaceae (CRE) is an important public health issue worldwide, not only due to the potential of these pathogens for widespread dissemination, but also due to the limited antimicrobial therapy options, and the elevated mortality rates associated with these infections. As with other multidrug-resistant organisms (MDROs), active surveillance via timely testing, early diagnosis, and contact isolation is an important strategy to control the occurrence and spread of CRE bacteria. Here we summarize the epidemiology of CRE infections in Japan from 2015 to 2019. Data were extracted from a public dataset collected by the nationwide surveillance system via the National Institute of Infectious Diseases (NIID) of Japan. The annual number of reported CRE infections has remained relatively stable, with a tendency to increase in the last two years (1671 cases reported in 2015 and 2333 cases reported in 2019). The majority of patients who presented CRE infections over this five year period were older than 65 years (~80%, mean age 75), 60% of them were men, and mortality rates were around 3.5%. Importantly, about 60% of infections are caused by both Enterobacter cloacae and Klebsiella aerogenes (previously known as Enterobacter aerogenes), the former being the most common pathogen in 2015 and 2016 (~30%), and the latter the leading pathogen since 2017 (~40%). The most common carbapenemase isolated was the IMP carbapenemase type. Further studies are needed to determine the prevalence of CRE colonization, especially in the healthcare setting, and to elucidate the mechanisms behind the local predominance of Klebsiella aerogenes and Enterobacter cloacae.